ASEAN Financial Integration - Almekinders, Geert (IMF Working Papers; Working Paper, 2015)
The establishment of the ASEAN Economic Community (AEC) at end-2015 has brought into sharp focus the issue of financial and economic integration in the region. This paper takes stock of ASEAN's financial integration and prospects. ASEAN integration could accelerate in the years ahead; it will likely be a safe, gradual process consistent with the 'ASEAN way' of consensus decision-making. Properly phased and sequenced, closer financial integration has the potential to help increase real incomes and accelerate real convergence within ASEAN and narrow the region's gap with advanced Asia. Realizing the promise of financial integration will require ASEAN countries to make long-term investments in financial infrastructure. Policymakers can draw on the experience of their more advanced peers and of other regions. Gradualism and safeguards should not be excuses for inaction or financial protectionism. Reliance on flexible policy frameworks and a strengthened and tested regional financial safety net should be part of the agenda. Closer engagement with the Fund could also help.